Witnessing and Disrupting: The Ethics of Working with Testimony for Refugee Advocacy. (2nd February 2018) - Kahn, Leora; Fábos, Anita H
Abstract: Testimonies of refugees and other forced migrants have helped stimulate and shape social change, and have on occasion been an effective tool for policy change and social transformation. But while advocacy on behalf of forcibly displaced people often demonstrates the best of intentions, many human rights advocates grapple unsuccessfully with the power differentials at all stages of the process. Using techniques derived from drama and experiential learning, the authors of this note learned to recognize narrative strategies and ethical dilemmas inherent in sharing, choosing, and representing the difficult subject matter produced by many refugees and forced migrants. By developing an embodied understanding of power relations, advocates struggling with the ethics of representation of refugee and forced migrant narratives can identify strategies for producing alternative narrative frames. Drawing from the results of a series of workshops provided to a mixed group of refugee service professionals, community leaders, journalists, artists, and academics, this note reflects upon our use of these practices as a way to encourage empathetic listening and develop strategies of narrative disruption for refugee advocacy.